The design and validation of an automatic email clustering system based on semantics - Cernian, A. S.; Florea, I.; Carstoiu, D.; Sgarciu, V. (2011 IEEE 6th International Conference on Intelligent Data Acquisition and Advanced Computing Systems, 2011)
Everybody has at least one email address nowadays. We keep in touch with family, friends, business partners by email. We receive news, notifications and advertisements by email. We subscribe to different newsletters that we also receive by email. But don't you hate it when your inbox gets all crowded with messages and you're having trouble finding exactly the one email you need? We all hate those moments. Common email clients allow us to sort emails by date, by sender or even by subject. But that is not always enough. This paper proposes the design and validation of an automatic system for clustering email messages based on semantic meaning. Our system is based on the clustering by compression technique, which has proven its capabilities during previous tests.